Pine Apple [sic] Plantation, Trinidad, B.W.I. - (:unkn) unknown (Waterman the Hatter, Clothier and Outfitter, Trinidad, 2009)
A picture of a pineapple field that stretches off into the distance with some of the plants having the fruit on them.
Colour: Black and White; Style: Portrait; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Pineapple--Trinidad and Tobago; Pineapple industry--Trinidad and Tobago; Agriculture--Trinidad and Tobago; [1930]; Fruit--Trinidad and Tobago; Fruit trade--Trinidad and Tobago